Teaching English for ESP students and technologies to use - Khalilova Himoyat Khatamovna (International Journal on Orange Technologies, 2021)
This article examines issues concerning ESP teaching and the most productive technologies to use in classes. To get fruitful results in ESP teaching English teacher is recommended to use following groups of components of the teaching technology discussed in this article